The Influence of Learning Students Teams Achievement Divisions (STAD) and Mind Map on Student Achievement of Biology Subject at SMA Negeri 1 Sigi - Tasriah, Tasriah; Jamhari, Mohammad; Rede, Amram (Jurnal Riset Pendidikan MIPA, 2017)
This study aimed to: determine the influence of STAD learning on student achievement, determine the influence of mind map on student achievement, and describe the influence of both interaction, STAD and mind maps to student achievement. This study is quantitative research with experimental factorial design. The study population are all students of grade X consists of 8 classes, grade XI consisting of 5 classes. Samples are 3 classes of grade X and 3 classes, of grade XI-Science. All samples taken by using purposive sampling technique. Data were obtained by results of student achievement afterwards analyzed with the Statistical Parametric two-way analysis of variance (two-way-ANOVA) assisted SPSS version 20. The results showed that: (1) There was a significant influence learning model STAD type on students achievement. (2) There was a significant influence on the mind map of student achievement. (3) There was a significant effect of interaction and learning models tipe STAD mind map technique on students achievement at SMA Negeri 1 Sigi. Based on the post hoc test to show the difference in the average for each treatment. So among the three treatments, more effective treatment were a combination of STAD learning and mind maps.